Victorious rebels and postwar politics. Issue 2 (2nd April 2016) - Lyons, Terrence
Abstract: Why do victorious rebels sometimes form powerful postwar political parties and other times collapse into weak, factionalized organizations? This paper examines cases of rebel victories in civil wars in Africa and traces the links between war duration, the extent of external intervention, and whether or not the war was fought in a compact area with the nature of the postwar political parties. It argues that protracted wars in confined territory with little external assistance have different organizational legacies than quick wars fought over expansive territory with significant international involvement. Four cases – Uganda, Ethiopia, Democratic Republic of Congo, and Libya – are used to illustrate the argument.